Perbandingan parasetamol dan petidin sebagai profilaksis menggigil pada pasien dengan anestesi spinal - Fadly Ramadhan; Luwih Bisono; Soejat Harto; Putri C. Eyanoer (Poltekkes Kemenkes Aceh, 2023)
Background: Shivering is a frequent complication in patients undergoing surgery under neuraxial anesthesia. Shivering can increase oxygen consumption and lead to hypothermia, so it must be prevented.Objectives: This study aims to determine the difference between intravenous paracetamol and pethidine to prevent shivering after spinal anesthesia.Methods: This research is a double-blind, randomized, controlled clinical trial. This research was conducted at Haji Adam Malik General Hospital, Medan. This research was done in August 2022. The research sample was patients with spinal anesthesia at the Haji Adam Malik General Hospital Medan who met the research criteria. The Modified Crossley and Mahajan Scale (1-4) measured the degree of shivering. The subjects who met the inclusion criteria were 34 patients, with 17 patients in the group receiving pethidine and 17 receiving paracetamol. The data that will be collected is analyzed with the bivariate test using the Chi-square test CI 95% to compare categorical variables. Of the 34 patients, 17 patients in the group received pethidine, and 17 patients in the group received paracetamol. Furthermore, both groups were randomized to obtain a balanced group of 17 patients in each group.Results: In this study, the degree of shivering in the paracetamol and pethidine groups did not show a statistically significant difference with the value (p= 0,450). However, the highest degree of shivering was found in the paracetamol group with a score of 2 (significant tremor in the chest muscles), about 17,6%. While in the pethidine group, most scores suffer shivering, the highest score being 1 (intermittent and mild tremors in the jaw and neck muscles).Conclusion: There is no difference in the effect of paracetamol and pethidine as shivering prophylaxis in preventing post-spinal anesthesia shivering.